Optical emission spectroscopy of radio frequency inductively coupled plasma for cold hydrogenation of nanoparticles. Issue 1 (January 2021) - Remes, Z; Kromka, A; Micova, J; Rezek, B; Poruba, A; Hsu, Hua-Shu
Abstract: The radio frequency inductively coupled plasma (ICP) offers an alternative "cold" way to affect the size, composition, structure, and surface functionality of nanoparticles (NPs), such as metal oxide NPs, providing further adjustment of their physical and chemical properties. The ICP was monitored in-situ by optical emission spectroscopy (OES). In particular, hydrogen, oxygen, argon, and nitrogen plasma was studied. OES data show that despite the decrease of the optical emission intensity with increasing gas pressure, the concentration of atomic hydrogen increases with pressure and radio frequency power.